"Little Red Sandals": female police officers' lived experience of investigating sexual violence. Issue 1 (27th November 2020) - Bozga, Adina; McDowall, Almuth; Brown, Jennifer
Abstract : Purpose: Against a background of increasing workload and external criticism, the purpose of this paper is to expose the indelible memories impressed on female police officers dedicated to investigating allegations of rape and sexual violence. Design/methodology/approach: Participants ( n = 15) were female police officers working in a specialist sexual offences investigation unit in a large English Metropolitan Police Force. A semi-structured interview was employed to elicit their experiences as an example of "extreme" police work. Interpretative phenomenological analysis was used to develop themes elucidating psychological and physical impacts on officers and their coping strategies. Findings: Personal consequences were framed within the conceptualisation of secondary trauma. Emergent findings revealed profound and lasting vicarious traumatisation. Participants reported feelings of depression, anxiety, suicidal ideation, intrusive imagery, altered beliefs and cognitions as well as disrupted intimacy with partners. Coping adaptations included sensory shutdown, avoidance, dissociation and a reduction in victim care. Practical implications: The findings support the need to consider occupational interventions to address risk factors associated with caseload, tenure, personal experience of neglect (e.g. in childhood), and the permeability of work and family boundaries for such exceptional policing tasks. Originality/value: The paper contributes to a nascent literature on stress in "extreme" police work. The theoretical contribution is the focus on the emotional and physical aspects of vicarious trauma, which have been less well understood than cognitive aspects. The practice implications stress the need for targeted support activities given the profound psychological consequences of prolonged exposure to distressing material.